The relationship between persistence, academic engagement and academic achievement among post graduate students of OUM - Lee, Nagarajah; Chung , Han Tek; Rahmah Hashim; Lim, Tick-Meng (Open University Malaysia (OUM), 2011)
Self directed and self manage learning is one of the pillar for lifelong learning. Learners’ stamina to sustain as self directed learners is vital for their academic success. This paper examines the association between persistence, academic engagement, and academic performance among post graduate students in an Open and Distance Learning Institution. The logistic regression was used to model the relationship while the Receiver Operating Curve (ROC) curve was used to assess the sensitivity and specificity of the predictive model. In this cross sectional a total of 390 students enrolled in various Master degree programs at OUM answer a self administered questionnaire. Academic performance was compared with students’ perceived engagement in academic activities, and persistence in studies. Among the significant predictors of academic performance are classroom and cognitive emphasis (components of engagement), and academic integration, service satisfaction, academic conscientiousness and degree commitment (components of persistence). Students with favorable ratings on their academic engagement and persistence in studies tend to do better academically. The statistical model predicting these relationships is 83.33% sensitive and 91.04% specific. Using student engagement and persistence as predictors of academic achievement would enable the academic institutions to identify ‘at risk’ students much earlier compared to using CGPA. (Abstract by authors)